Graphene‐Protected 3D Sb‐based Anodes Fabricated via Electrostatic Assembly and Confinement Replacement for Enhanced Lithium and Sodium Storage. Issue 45 (12th October 2015) - Ding, Yuan‐Li; Wu, Chao; Kopold, Peter; van Aken, Peter A.; Maier, Joachim; Yu, Yan
Abstract : Alloy anodes have shown great potential for next‐generation lithium‐ion batteries (LIBs) and sodium‐ion batteries (SIBs). However, these applications are still limited by inherent huge volume changes and sluggish kinetics. To overcome such limitations, graphene‐protected 3D Sb‐based anodes grown on conductive substrate are designed and fabricated by a facile electrostatic‐assembling and subsequent confinement replacement strategy. As binder‐free anodes for LIBs, the obtained electrode exhibits reversible capacities of 442 mAh g −1 at 100 mA g −1 and 295 mAh g −1 at 1000 mA g −1, and a capacity retention of above 90% (based on the 10th cycle) after 200 cycles at 500 mA g −1 . As for sodium storage properties, the reversible capacities of 517 mAh g −1 at 50 mA g −1 and 315 mAh g −1 at 1000 mA g −1, the capacity retention of 305 mAh g −1 after 100 cycles at 300 mA g −1 are obtained, respectively. Furthermore, the 3D architecture retains good structural integrity after cycling, confirming that the introduction of high‐stretchy and robust graphene layers can effectively buffer alloying anodes, and simultaneously provide sustainable contact and protection of the active materials. Such findings show its great potential as superior binder‐free anodes for LIBs and SIBs. Abstract : Using a facile electrostatic assembly and graphene‐confined replacement strategy, 3D Sb‐based anodes grown on nickel foam (NF) are designed and fabricated by utilizing NF as both reductant and substrate. When employed as a binder‐free anode for lithium and sodium storage, the prepared product shows superior rate capability and stable cyclability. In addition, the obtained 3D structure maintains good structural stability upon cycling.